Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1162/ajhe_a_00073
|View full text |Cite
|
Sign up to set email alerts
|

Second Trimester Sunlight and Asthma: Evidence from Two Independent Studies

Abstract: One in twelve Americans suffers from asthma and its annual costs are estimated to exceed $50 billion. Simultaneously, the root causes of the disease remain unknown. A recent hypothesis speculates that maternal vitamin D levels during pregnancy affect the probability the fetus later develops asthma. In two large-scale studies, we test this hypothesis using a natural experiment afforded by historical variation in sunlight, a major source of vitamin D. Specifically, holding the birth location and month fixed, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Environmental exposures such as bright light, and pollution were all found to be associated with epigenetic changes in adiposity leading to higher GWG [ 8 , 9 , 11 ]. At current times, more studies are required to determine the role of sunlight exposure to pregnancy outcomes as some past studies showed a positive effect on asthma when pregnant women received proper sunlight exposure in the second trimester [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposures such as bright light, and pollution were all found to be associated with epigenetic changes in adiposity leading to higher GWG [ 8 , 9 , 11 ]. At current times, more studies are required to determine the role of sunlight exposure to pregnancy outcomes as some past studies showed a positive effect on asthma when pregnant women received proper sunlight exposure in the second trimester [ 12 ].…”
Section: Introductionmentioning
confidence: 99%